Tanner's law - West, Charles (Berkley, 2022)
"Tanner Bland leaves his Virginia home on foot to fight for Dixie and rides back on a fine horse. Most folks would call that a profit--until they consider his loss. With everyone thinking the soldier dead, his younger brother marries Tanner's fiancée hours before he returns. His home no longer his own, Tanner heads west to join an old army pal and hit the gold mines of Montana. But the wagon train the men join is not what they are hoping for. In the train with them are the four Leach brothers, each one meaner than the next. Now, if Tanner and his buddy want to make it to Montana alive, they'll have to keep their enemies close...and their weapons closer." --